TO FIND OUT THE DIFFERENCE IN AGE, GENDER and EDUCATIONAL STATUS OF PEOPLE WITH TEMPORAL LOBE EPILEPSY IN ANXIETY - Manish Kumar Meel (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Neurological diseases in India contribute to the huge morbidity rate and prevalence of epilepsy among adults from 1.2 to 11.9 per 1000 population and the reported incidence of epilepsy in India vary from 0.2 to 0.6per population. Epilepsy is one among the disorders which is significantly associated to have psychological and social consequences for everyday living. Hence there is a huge need for research in exploring mental health management strategies. Epilepsy affects biological, psychological and cognitive features and influences the quality of life. Epilepsy is a syndrome with complex and multiple components involved. People with any age can be affected with epilepsy. Material and methods: This study was conducted in the dept. of Psychiatry. People diagnosed with epilepsy after a clinical examination by the Neurologist after confirmatory diagnostic investigations for temporal lobe epilepsy were selected for the study. People with temporal lobe epilepsy are screened to assess the level of memory, anger, anxiety and quality of life. Sample size is determined assuming 95 % confidence interval and margin of error (E =1)1%. Literature revealed high effect size for psychotherapy with cognitive behaviour therapy and memory training in people with epilepsy. Result: The mean value of people with temporal lobe epilepsy in overall anxiety before and after anxiety management training is 48.63 and 37.75 respectively and SD is 11.03 and 8.62 respectively. The t - value is 6.16 is found to be significant. This shows that there is significant reduction in overall anxiety after the memory training program. Conclusion: The data of this study suggest that there may be no gender difference in the prevalence of epilepsy comorbidity of anxiety and depression, but gender discrepancy plays a significant role in the incidence of psychiatric comorbidities in epilepsy. There is a significant increase in memory and quality of life after memory training and quality of life enhancement program; significant decrease in anger and anxiety after anger and anxiety management program for people with temporal lobe epilepsy. Keywords: Temporal Lobe, Epilepsy, Anxiety and Educational status